Laparoscopic Inguinal Hernia Surgery - Morelli Brum, Raúl (Cirugía del Uruguay, 2005)
The purpose of this paper is to enhance treatment of inguinal hernia through a bibliographic study of its main complications and the analysis of a retrospective series of /aparoscopic restorations performed by the author in the same prívate medica/ care center. From Oecember 1994 through Ju/y 2003, ninetynine patients were operated in 108 procedures. The technique employed was trans-abdominal preperitonea/ (TAPP) Follow-up covered over 2 years in 80% of patients with a re/apse of 2.8%. Main morbility was neuralgia due to a nerve being trapped, which fact required re-intervention. There was no mortality.